2017
DOI: 10.1016/j.nme.2017.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and origin of large size dust particles produced in the Alcator C-Mod tokamak

Abstract: International audiencePost mortem analyses of dust collected in Alcator C-Mod have highlighted a production of large size dust particles. The quantities of such large particles are higher than in any other tokamak. They are divided in two classes as a function of their shape and consequently, their origin. Rounded dust particles such as spheres and splashes constitute the first class. These particles are the result of high heat loads on various leading edges of plasma facing components and possibly, their melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Beryllium particulate ejection has also been observed as a result of disruptions in JET equipped with its ITER-Like Wall, illustrating that even at comparatively low stored energies, Be melting can and does occur [11]. Post-mortem examination of in-vessel surfaces and of PFCs extracted from the machine clearly show the presence of re-solidified droplets in the vicinity of melted regions (similar observations have also been made on molybdenum tiles in Alcator C-Mod [12]). …”
Section: Introductionsupporting
confidence: 54%
“…Beryllium particulate ejection has also been observed as a result of disruptions in JET equipped with its ITER-Like Wall, illustrating that even at comparatively low stored energies, Be melting can and does occur [11]. Post-mortem examination of in-vessel surfaces and of PFCs extracted from the machine clearly show the presence of re-solidified droplets in the vicinity of melted regions (similar observations have also been made on molybdenum tiles in Alcator C-Mod [12]). …”
Section: Introductionsupporting
confidence: 54%
“…However, experiments have shown that the combination of different phenomena (e.g. melting of edges of PFC, material fatigue, intense particle fluxes, material erosion followed by accretion in the plasma edge, …), particularly during off normal events such as Edge Localized Modes (ELMs) or disruptions, can trigger the formation in the plasma chamber of particles with variable size, ranging from tens of nanometers to hundreds of micrometers [2,3,4,5]. Due to expected much higher energy outflows in ITER compared to the currently operating tokamaks, larger quantities of dust could be produced.…”
Section: Introductionmentioning
confidence: 99%
“…Outwith astrophysics, in magnetically confined fusion, material sputtered from the vessel walls has an elongated geometry (e.g. Arnas et al (2017)) and can disrupt the optimum operation of the device when it migrates through the plasma. Understanding the growth and evolution of such dust can help mitigate disruption and enhance operation.…”
Section: Discussionmentioning
confidence: 99%